Preparation and Crystallization Property of Ternary Composites of WBG/AA-RCC/PP - Jiang Zhu; Haitao Ni; Xiaoqing Liao; Xiang Liu (Journal of Chemistry)
A series of ternary composites of WBG/AA-RCC/PP were prepared and their crystallization behaviors were investigated by XRD and DSC. The results indicate that WBG and AA-RCC affect the crystallization of PP matrix with a mutual inhibition effect. This effect is enhanced with increasing content of WBG and induces the growth of β2 crystal. AA-RCC promotes the heterogeneous nucleation of α crystal and offers a template for α crystal growth along a specific lattice plane and promotes the epitaxial crystallization of PP matrix, while the specific arranged α crystal could induce the formation of β crystal.